Epigenetic silencing of tumor suppressor candidate 3 confers adverse prognosis in early colorectal cancer - Burgermeister, Elke; Höde, Patrick; Betge, Johannes; Gutting, Tobias; Merkel, Andreas; Nowak, Daniel; Rückert, Felix; Sticht, Carsten; Breitkopf-Heinlein, Katja; Schulte, Nadine; Härtel, Nicolai; Belle, Sebastian; et al. (OncoTarget, 2017)
Colorectal cancer (CRC) is a biologically and clinically heterogeneous disease. Even though many recurrent genomic alterations have been identified that may characterize distinct subgroups, their biological impact and clinical significance as prognostic indicators remain to be defined. The tumor suppressor candidate-3 (TUSC3/N33) locates to a genomic region frequently deleted or silenced in cancers. TUSC3 is a subunit of the oligosaccharyltransferase (OST) complex at the endoplasmic reticulum (ER) which catalyzes bulk N-glycosylation of membrane and secretory proteins. However, the consequences of TUSC3 loss are largely unknown. Thus, the aim of the study was to characterize the functional and clinical relevance of TUSC3 expression in CRC patients’ tissues (n=306 cases) and cell lines. TUSC3 mRNA expression was silenced by promoter methylation in 85 % of benign adenomas (n=46 cases) and 35 % of CRCs (n =74 cases). Epidermal growth factor receptor (EGFR) was selected as one exemplary ER-derived target protein of TUSC3-mediated posttranslational modification. We found that TUSC3 inhibited EGFR-signaling and promoted apoptosis in human CRC cells, whereas TUSC3 siRNA knock-down increased EGFR-signaling. Accordingly, in stage I/II node negative CRC patients (n=156 cases) loss of TUSC3 protein expression was associated with poor overall survival. In sum, our data suggested that epigenetic silencing of TUSC3 may be useful as a molecular marker for progression of early CRC.